Biogeochemical Coring and Preservation Method for Unconsolidated Soil Samples. Issue 3 (10th June 2021) - Landis, Richard; Hua, Han; Yin, Xin; Axe, Lisa; Morgan, Scott
Abstract: Developing an accurate conceptual site model (CSM) is an important process before a decision can be made regarding effective remedial actions. A critical aspect of an accurate CSM is thoroughly understanding the biogeochemistry occurring at the site in the area of concern. To collect media samples that accurately preserve the in situ biogeochemistry, a new Rotosonic core barrel and core preservation protocol was developed. The new biogeochemical core barrel (BCB) successfully isolated and preserved the in situ biogeochemical conditions of the soil core and minimized the soil core's exposure pathways to air. The BCB's success was achieved by a modified Rotosonic core barrel, a specialized drive shoe, an internal BCB core barrel piston, hydraulic extrusion of the soil core into a stainless core tube with an internal piston, and specialized core tube sealing, handling, and subsampling methods. Detailed subsampling of 65‐foot (nominally 20 m) soil core in 2‐inch (nominally 51 mm) increments within a specialized anaerobic glovebox confirmed the presence of five biogeochemical redox transition zones within the soil core. The BCB also allowed for split soil core samples for detailed mineralogical and live microbiological studies. Success of the BCB method is further evidenced by the presence of the highly redox‐sensitive surface bound iron sulfide mineral mackinawite. The BCB allowed detailed analysis of the soil core including Fe and S concentration gradients, oxidation–reduction potential gradients, volatile organic compound analysis, and live microbiological assessments. Abstract : Article impact statement : A new method was demonstrated for collecting soil core samples and preserving in situ redox conditions to identify biogeochemical transitions.